(untitled) (Bangladesh Rice Journal, 2019)
Field performance of low land weeder was evaluated in mechanically transplanted rice fieldat Bahirbagh and Provakordi representing the silty loam soil under Gopalganj district of Bangladesh during the non-irrigated wet season (Aman) 2016. Twenty-one-day-old seedlings were transplanted by walk behind type 4-rows mechanical rice transplanter (DP480) at a pre-set spacing of 300 × 170 mm. Randomized Complete Block (RCB) design with three replications was applied with weeding practices of BRRI weeder (BW) followed by (fb) one hand weeding (HW), BRRI power weeder (BPW) fb one HW, two HW, pyrazosulfuron-ethyl (PSE) fb one HW, weedy check, weed free and mulching fb two HW (farmers’ practice) in two locations. The common weed species were observed in experimental sites. Weeding efficiency (WE) of BPW and BW was 67 and 44, respectively. Field capacity of BPW and BW was obtained 0.07 and 0.03 ha hr-1, respectively. Operator’s skill influenced the performance of weeder. During operation, BPW damaged 14-15% tillers in both the locations. However, damaged plants were revived after few days. The labour requirement in BW fb one HW, BPW fb one HW, PSE fb one HW and two HW were 380, 362, 243 and 616 man-hr ha-1 respectively. Except weedy check, weed management practices showed identical grain yield in both the locations. The BCR was accounted in PSE fb one HW (1.35), BW fb one HW (1.21), BPW fb one HW (1.20) whereas the lowest BCR was observed in weedy (0.83) and two HW (1.00). It can be concluded that pyrazosulfuron-ethyl, BRRI power weeder followed by one hand weeding and BRRI weeder followed by one hand weeding appeared as the cost effective weed control methods in mechanically transplanted Aman rice production. Bangladesh Rice j. 2018, 22(1): 25-34